Studies on physicochemical characters of fruits of Date palm genotypes (Indian Journal of Arid Horticulture, 2025)
In Kachchh region of Gujarat, variability with respect to berry colour, weight, pulp content, fruit size, taste, bunch size and yield potential were observed in date palm orchards. A survey was carried out to identify suitable genotypes of date palm (Phoenix dactylifera L.) based on the fruit quality and yield attributing characters. Fruits of ten elite types were collected and physicochemical characters were studied. The genotypes showed considerable variation in morphological and physicochemical characters of fruits. The colour of berry at doka stage was yellow, red to dark red. Variation in fruit weight from 7.71 to 17.4g, stone weight 0.81-1.50g., TSS 19.8 -36.2 brix and acidity 0.18-0.40% was recorded. The suckers of identified genotypes DP-01 and DP -03 would be procured for multiplication and evaluation under hot arid region and it can be further utilized for improvement programme.
Keywords: Date palm; Phoenix dactylifera; variability; genotypes; fruit quality